Ad hoc networks : 9th International Conference, AdHocNets 2017, Niagara Falls, ON, Canada, September 28-29, 2017 : proceedings /: 9th International Conference, AdHocNets 2017, Niagara Falls, ON, Canada, September 28-29, 2017 : proceedings. ([2018]) - Unknown
No abstract available